3-{2-[(1,3-Benzothiazol-2-yl)sulfanylmethyl]phenyl}-4-methoxy-5,5-dimethylfuran-2(5H)-one - Duan, Anna (International Union of Crystallography, 2012)
In the title compound, C(21)H(19)NO(3)S(2), the dihedral angles formed between the thiazole ring and the adjacent benzene ring and the other benzene ring are 1.58 (3) and 76.48 (6)°, respectively. The crystal structure features a weak C—H⋯O interaction.